Muscovite (mica) allows the characterisation of supported bilayers by ellipsometry and confocal fluorescence correlation spectroscopy - Benes, Martin; Billy, Didier; Hermens, Wim T; Hof, Martin (Biological chemistry, 2002)
We demonstrate for the first time that ellipsometry and confocal fluorescence correlation spectroscopy (FCS) are complementary methods for the characterisation of supported planar phospholipid bilayers (SPBs) formed on mica, a mineral used in atomic force microscopy investigations of SPBs. Addition of small unilamellar vesicles containing 20% dioleoyl-phosphatidylserine (DOPS) and 80% dioleoyl-phosphatidylcholine (DOPC) to an oxidised borosilicate surface, on the other hand, results in a planar lipid system characterised by lateral diffusion coefficients which are three time smaller than those obtained for SPBs. Moreover, seven labelled phospholipids were tested for their suitability in the FCS characterisation of vesicles as well as of SPBs.
Keywords: Microscopy, Fluorescence; Lipid Bilayers; povrchové vlastnosti; Aluminum Silicates; Microscopy, Confocal; fosfatidylcholiny; sloučeniny boru; fluorescenční mikroskopie; konfokální mikroskopie; fúze membrán; Membrane Fusion; Phosphatidylserines; Silicates; lipidové dvojvrstvy; Phospholipids; Surface Properties; Boron Compounds; fosfatidylseriny; fosfolipidy; Phosphatidylcholines; silikáty hliníku; silikáty